1998
DOI: 10.1080/0266736980130406
|View full text |Cite
|
Sign up to set email alerts
|

Cross-age Peer Mentoring in Action: the process and outcomes

Abstract: This article describes the setting up and running of a peer-mentoring scheme. Year10 (Y10) mentors from a large city comprehensive school worked with Year 6 (Y6) students in four of its feeder primary schools. This article aims to present one model of mentoring between schools, describing the process and outcomes for both mentors and mentees, and also to promote reflection and discussion about the role of peer support particularly in relation to transition between primary and secondary schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Thompson and Smith (2011) found that mentors felt they had learned to deal with difficult situations, and developed communication skills, problem-solving skills and increased confidence. In a small-scale single-time point study in an English secondary school, the majority of peer supporters agreed with statements relating to improved interpersonal skills and personal development (Dearden, 1998). Karcher, Davidson, Rhodes, and Herrera (2010) suggest that cross-age peer mentoring promotes mentors' developmental competencies, citing evidence from US evaluations including Pastoral Care in Education 105 improvements in academic engagement and self-esteem.…”
Section: Introductionmentioning
confidence: 96%
“…Thompson and Smith (2011) found that mentors felt they had learned to deal with difficult situations, and developed communication skills, problem-solving skills and increased confidence. In a small-scale single-time point study in an English secondary school, the majority of peer supporters agreed with statements relating to improved interpersonal skills and personal development (Dearden, 1998). Karcher, Davidson, Rhodes, and Herrera (2010) suggest that cross-age peer mentoring promotes mentors' developmental competencies, citing evidence from US evaluations including Pastoral Care in Education 105 improvements in academic engagement and self-esteem.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, the current study employed the strategy of using cross-age peers (i.e., students in higher grade levels who help younger students). The use of cross-age peers has been cited as an effective influencer of younger youth due to perceptions of increased message credibility (Dearden 1998). The intervention therefore combines two components-media and peers-with each having considerable potential to influence attitudes and behaviors related to violence.…”
Section: Introductionmentioning
confidence: 98%
“…Mentors require appropriate and relevant knowledge and experience of both life and learning. When both pupils and mentor alike enjoy the companionship provided by a tutoring relationship, the potential for learning is usually greater (Dearden, 1998).…”
Section: Approaches To Mentoringmentioning
confidence: 99%
“…They can also establish a way of learning-learning from one another-which may well be the main informal learning mode in life after school. Peer mentoring has the potential for embedding it in the curriculum (Dearden, 1998).…”
Section: Other Forms Of Mentoringmentioning
confidence: 99%